A decade of underwater noise research in support of the European Marine Strategy Framework Directive. (1st September 2022) - Merchant, Nathan D.; Putland, Rosalyn L.; André, Michel; Baudin, Eric; Felli, Mario; Slabbekoorn, Hans; Dekeling, René
Abstract: Underwater noise from human activities is now widely recognised as a threat to marine life. Nevertheless, legislation which directly addresses this source of pollution is lacking. The first (and currently only) example globally is Descriptor 11 of the Marine Strategy Framework Directive (MSFD), adopted by the European Union in 2008, which requires that levels of underwater noise pollution do not adversely affect marine ecosystems. The MSFD has stimulated a concerted research effort across Europe to develop noise monitoring programmes and to conduct research towards specifying threshold values which would define 'Good Environmental Status' (GES) for underwater noise. Here, we chart the progress made during the first decade of Descriptor 11's implementation: 2010–2020. Several international joint monitoring programmes have been established for impulsive and continuous noise, enabling ecosystem-scale assessment for the first time. Research into the impact of noise on individual animals has grown exponentially, demonstrating a range of adverse effects at various trophic levels. However, threshold values for GES must be defined for 'populations of marine animals.' Population-level consequences of noise exposure can be modelled, but data to parameterise such models are currently unavailable for most species, suggesting that alternative approaches to defining GES thresholds will be necessary. To date, the application of measures to reduce noise levels (quieting/noise abatement) has been limited. To address this, the EU in 2021 identified an explicit need to reduce underwater noise pollution in its waters. Delivering on this ambition will require further research focused on the development and implementation of quieting measures. Highlights: Marine Strategy Framework Directive (MSFD) is first legislation globally to address underwater noise pollution explicitly. MSFD is acting as a global test case for management of cumulative noise levels. Several international joint monitoring programmes established in first decade of MSFD. Threshold values still needed to define Good Environmental Status for noise. Development and implementation of quieting measures needed to reduce adverse effects.